Ultralong Polymeric Room Temperature Phosphorescence Materials Fabricated by Multiple Hydrogen Bondings Resistant to Temperature and Humidity. Issue 21 (21st August 2021) - Zhu, Yan; Guan, Yan; Niu, Yifan; Wang, Pu; Chen, Renjie; Wang, Yanhao; Wang, Ping; Xie, He‐Lou
Abstract: Polymeric room temperature phosphorescence (RTP) materials have attracted tremendous attentions owing to their excellent flexibility, easy processing, low cost, and good thermal stability. In this work, an improved strategy is proposed for ultralong RTP polymeric materials through copolymerizing the phosphor monomer with D (donor)−A (acceptor) structure and another monomer with ultrastrong multiple hydrogen bonds. A series of copolymers (P1–P4) containing different ratios of carbazole‐dibenzofuran (CDF) and ureidopyrimidinone (UPy) segments are successfully prepared. The obtained copolymers show ultralong phosphorescence lifetimes between 1.70 and 2.16 s with afterglow duration time between 15 and 17 s. The multiple hydrogen bonds of UPy groups can promote extremely intermolecular and intramolecular interactions, which immobilize the phosphors to prevent nonradiative transitions. Especially, these interactions lead to the copolymers can be robustly resistant to high temperature and humidity. Flexible and foldable anti‐counterfeiting with high temperature and humidity resistant features are achieved, which would be applied in practical special environments. Abstract : Polymeric room temperature phosphorescence (RTP) materials play an increasingly important role in optoelectronics, anti‐counterfeiting and data security technologies areas. In this paper, ultralong phosphorescence lifetime of 2.16 s and decent quantum efficiency are obtained from polymers containing ultrastrong hydrogen bonds. In addition, this kind of RTP polymers show high temperature resistance and insensitiveness to water.